The Midterm Surgical Outcome of Modified Expansive Open-Door Laminoplasty - Kuang-Ting Yeh (BioMed Research International, 2016)
Laminoplasty is a standard technique for treating patients with multilevel cervical spondylotic myelopathy. Modified expansive open-door laminoplasty (MEOLP) preserves the unilateral paraspinal musculature and nuchal ligament and prevents facet joint violation. The purpose of this study was to elucidate the midterm surgical outcomes of this less invasive technique. We retrospectively recruited 65 consecutive patients who underwent MEOLP at our institution in 2011 with at least 4 years of follow-up. Clinical conditions were evaluated by examining neck disability index, Japanese Orthopaedic Association (JOA), Nurick scale, and axial neck pain visual analog scale scores. Sagittal alignment of the cervical spine was assessed using serial lateral static and dynamic radiographs. Clinical and radiographic outcomes revealed significant recovery at the first postoperative year and still exhibited gradual improvement 1–4 years after surgery. The mean JOA recovery rate was 82.3% and 85% range of motion was observed at the final follow-up. None of the patients experienced aggravated or severe neck pain 1 year after surgery or showed complications of temporary C5 nerve palsy and lamina reclosure by the final follow-up. As a less invasive method for reducing surgical dissection by using various modifications, MEOLP yielded satisfactory midterm outcomes.